Prescribing Opioids for Chronic Noncancer Pain in Primary Care: Risk Assessment. Issue 5 (September 2014) - Gordon, Allan; Cone, Edward J.; DePriest, Anne Z.; Axford-Gatley, Robert A.; Passik, Steven D.
Abstract : : The use of opioids for patients with chronic noncancer pain has increased dramatically, and with increasing use there is increasing concern about the potential for abuse and addiction during long-term treatment. Clinicians should avoid viewing formal or subjective risk assessment as a means of classifying patients into 2 distinct categories: compliant patients and substance abusers. The provider who perceives a patient as compliant may have a complacent attitude toward aberrant drug-related behavior, presuming that these signs reflect inadequately controlled pain, to be addressed by dose escalation. The provider who perceives a patient as a substance abuser may refuse to provide treatment for pain, leaving the patient to seek either illicit drugs or prescribed treatment from another provider. In fact, in seemingly compliant patients, any noncompliant use of opioids presents a safety risk regardless of the explanations offered. Even in known or suspected drug abusers, chronic pain warrants the use of adequate pharmacotherapy, although treatment in such cases may exclude drugs with high abuse potential. Thus, all aberrant drug-related behavior should be addressed within a treatment plan that combines adequate pain care with suitable interventions for the aberrant behavior, following current best practice strategies. This approach is consistent with the approach taken with other health conditions, such as diabetes or hypertension, for which it is understood that noncompliance with therapy presents a risk of harm.